Female Schooling, Non-Market Productivity, and Labor Market Participation in Nigeria - Adebayo B. Aromolaran (Yale University, Economic Growth Center, 2004)
Economists have argued that increasing female schooling positively influences the labor supply of married women by inducing a faster rise in market productivity relative to non-market productivity. I use the Nigerian Labor Force Survey to investigate how own and husband's schooling affect women's labor market participation. I find that additional years of postsecondary education increases wage market participation probability by as much as 15.2%. A marginal increase in primary schooling has no effect on probability of wage employment, but could enhance participation rates in self-employment by about 5.40%. These effects are likely to be stronger when a woman is married to a more educated spouse. The results suggest that primary education is more productive in non-wage work relative to wage work, while postsecondary education is more productive in wage work. Finally, I find evidence suggesting that non-market work may not be a normal good for married women in Nigeria.
Keywords: I21; J22; J24; O15; 330; Nigeria; Female Schooling; Women's Labor Market Participation; Non-Market Productivity; Weibliche Arbeitskräfte; Bildungsverhalten; Allgemeinbildende Schule; Produktivität; Nigeria